Giant coronary artery aneurysms in an infant with Kawasaki disease: Evaluation by echocardiography and computed tomographic angiography. Issue 10 (12th August 2018) - Cameron, Scott A.; Robinson, Joshua D.; Carr, Michael R.; Patel, Angira
Abstract : Kawasaki disease (KD) is a vasculitis that affects medium‐sized arteries and can lead to coronary artery aneurysms. KD should be considered in any infant presenting with prolonged fever. Delaying treatment beyond Day 10 of fever portends a high risk of coronary artery aneurysms. Echocardiography is often necessary to diagnose KD in young infants who frequently present without classic physical examination findings. We report on a case of KD with giant aneurysms in a 2‐month‐old infant. A combination of transthoracic echocardiography and CT angiography was utilized in the diagnosis as well as in the management of this infant.